Interventions for recurrent embryo implantation failure: An umbrella review - Abdulla Almohammadi (14158848) (2024)
Background Recurrent implantation failure (RIF) has a multifactorial etiology. An umbrella review was undertaken to evaluate the multiple proposed interventions. Objectives To summarize and assess the strength of evidence of interventions for RIF from published systematic reviews (SR) of randomized clinical trials (RCTs). Search Strategy After prospective registration (PROSPERO CRD42023414255), a systematic search was conducted in the Cochrane Library, Scopus and Medline from inception until March 2024. Selection Criteria SRs of RCTs, with or without meta‐analyses (MA), were included if they reported clinical pregnancy rates (CPR) or live birth rates (LBR). Data Collection and Analysis The methodological quality of the included SRs was appraised independently in duplicate using the AMSTAR 2 tool. For each intervention, the MAs of RCTs with statistically significant improvements were counted as a percentage of the total assessing the strength of evidence using the GRADE system. Main Results A total of 47 SRs were included: 32 reviews covered immunomodulatory interventions, 10 (68 RCTs) covered uterine and endometrial interventions, one covered antibiotics, and four (69 RCTs) addressed mixed approaches, including laboratory interventions. AMSTAR 2 appraised 41 (88%) SRs as critically low or low, and 6 (12%) as moderate or high in quality. The SRs often had a level of overlap of RCTs (median 33.3%), inconsistent definitions of RIF, and varied comparisons for the interventions. Considering the significant meta‐analytic evidence of high‐moderate GRADE strength: Granulocyte colony‐stimulating factor (G‐CSF) showed improvement in CPR in 9/13 (69.2%) MAs and LBR in 1/7 (14%); intralipid infusion showed improvement in CPR in 4/6 (57.14%) MAs and LBR in 3/4 (75%); peripheral blood mononuclear cells (PBMC) showed improvement in CPR in 4/8 (50%) MAs and LBR 3/5 (60%); platelet‐rich plasma (PRP) intervention showed improvement in CPR in 6/10 (60%) MAs and LBR in 1/5 (20%); human chorionic gonadotropins showed improvement in CPR in 3/3 (100%) MAs; growth hormone showed improvement in CPR in 1/1 (100%) MA; low molecular weight heparin showed improvement in CPR in 1/1 (100%) MAs and LBR in 1/2 (50%); hysteroscopy showed improvement in CPR in 1/2 (50%) MAs; and, intentional endometrial injury showed improvement in CPR in 3/4 (75%) MAs and LBR in 2/3 (66.66%). Conclusions Evidence syntheses of RCTs evaluating interventions for RIF suggest a consistent direction, with high to moderate strength, indicating that immunomodulatory treatments, including G‐CSF, PBMC, PRP, intralipid infusion, and intentional endometrial injury are likely to be effective. However, this conclusion should be interpreted with caution due to the generally low methodological quality of the included studies and the clinical heterogeneity observed in most SRs. Other Information Published in: International Journal of Gynecology & Obstetrics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ijgo.16066